Claiming church as a space for healing and re-authoring pastoral support for those abused in intimate partner relationships - Dlamini, Zamantshali (Stellenbosch Theological Journal, 2025)
Social Justice frameworks continue to challenge citizenship. The notion of disabling oppressive powers and systems has remodelled a new consciousness around human rights, diversity, inclusion, and liberation for humanity. Within the church landscape, it has also gained traction, uncovering oppressive Christian tradition and patriarchal ideologies that have negatively affected women in various facets e.g., socially, economically, and mentally. Feminist thinkers like Schuller Fiorenza have flagged gender blindness in reading Paul’s letters, advocating for radical equality. Joining the voices of many feminist pastoral practitioners who are advocating for liberation, this paper reimagines transformational reading of the Bible particularly the reading of Galatians 3:28 and 1 Corinthians 7 as a means of claiming space for women. The paper also envisions braver spaces necessitating pastoral praxis by privileging women’s lived experiences. Voices emerging in academic spaces are making a phenomenal contribution to necessitating feminist consciousness and creating awareness about the systemic and structural layers of oppression where the marginalized can embrace their vulnerability and build solidarity support through listening to others’ experiences. This contribution is far from changing the landscape, as it disrupts theologies that have for the longest time a seedbed for male domination. Advocacy work around gender-based violence and academic work done on domestic violence has broken the silence about the abuse in the church. Toxic theologies that pinned down women survivors to stay in abusive marriages are the subject that is constantly interrogated as a means of holding the clergy and women accountable. More of such salvific work is geared toward healing men’s consciousness because patriarchy harms men with all its forms of oppressive systems, practices, and cultures that perpetuate gendered abuse. One critical question of all time is, where to from now? Black women who are survivors of violence in their homes have grasped how situations led to the reality of their oppression, they can name their pain. Yet, they remain stuck in defining what it is like to claim space for their healing and reconceiving change without being harmed. How does the church navigate conversations that affirm women survivors so that they bounce back and thrive in their social circles? What intervention strategies and resources can the church employ in accompanying the GBV survivors toward their healing and wholeness? What alternatives can offer social change? This paper asks a critical question – How can faith spaces as well as community practitioners engage GBV survivors on theological processes and resources to enable debriefing? The paper intends to reflect on how the bible can be a vital tool to affirm those whose lived experiences include gender-based violence mainly in intimate relationships. The engagement thereof makes claims that the church can redeem itself by becoming an invented space for healing so that all those who profess Imago Dei can be seen and heard such that they thrive, witnessing to the God of justice.